Economic evaluations of lymphatic filariasis interventions: A systematic review and research needs - Gedge, LM; Bettis, A; Bradley, MH; Hollingsworth, TD; Turner, H (BioMed Central, 2018)
In 2000, the World Health Organization established the Global Programme to Eliminate Lymphatic Filariasis (GPELF), with the goal of eliminating the disease as a public health problem by 2020. Since the start of the programme, a cumulative total of 6.2 billion treatments have been delivered to affected populations - with more than 556 million people treated in 2015 alone. In this paper, we perform a rigorous systematic review of the economic evaluations of lymphatic filariasis interventions have been conducted. We demonstrate that the standard interventions to control lymphatic filariasis are consistently found to be highly cost-effective. This finding has important implications for advocacy groups and potential funders. However, there are several important inconsistencies and research gaps that need to be addressed as we move forward towards the 2020 elimination goals. One of the most important identified research gaps was a lack of evaluation of new interventions specifically targeting areas co-endemic with onchocerciasis and Loa loa - which could become a major barrier to achieving elimination.